The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1093/jee/101.4.1331
|View full text |Cite
|
Sign up to set email alerts
|

Within-Plant Distribution of Onion Thrips (Thysanoptera: Thripidae) in Onions

Abstract: Two aspects of the within-plant distribution of Thrips tabaci Lindeman (Thysanoptera: Thripidae) on onion, Allium cepa L., plants were investigated: 1) diurnal variations in the distribution of adults and larvae between basal and upper sections of onion leaves, and 2) between-leaf and within-leaf distribution of the eggs. The diurnal investigations showed that higher proportions of larvae than of adults congregated at the basal sections of plants, particularly when plants were young and thrips density was low.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…On a within-plant level, Sites et al (1992) observed that during the onion vegetative stage, T. tabaci populations were concentrated on the center leaves but progressively populations became equally distributed all over the leaves. Mo et al (2008) observed that when onion plants were young and T. tabaci densities were low, higher numbers of larvae than adults gathered at the base of plants. When onion plants matured and thrips densities increased, the larvae dispersed to other parts of the leaves.…”
Section: Seasonal Patterns Of T Tabaci On Hosts In the Onion Croppinmentioning
confidence: 97%
“…On a within-plant level, Sites et al (1992) observed that during the onion vegetative stage, T. tabaci populations were concentrated on the center leaves but progressively populations became equally distributed all over the leaves. Mo et al (2008) observed that when onion plants were young and T. tabaci densities were low, higher numbers of larvae than adults gathered at the base of plants. When onion plants matured and thrips densities increased, the larvae dispersed to other parts of the leaves.…”
Section: Seasonal Patterns Of T Tabaci On Hosts In the Onion Croppinmentioning
confidence: 97%
“…Many insect pests are known to be nonrandomly distributed within single plants (Kennedy and Booth 1951, Liu and Sengonca 1997, Mo et al 2008, Kumar et al 2014). Cabbage aphid colonies in the small plot trial were spatially aggregated vertically, starting on the abaxial side of leaves in the bottom portion of the canopy and moving to the racemes over the 7-wk period.…”
Section: Discussionmentioning
confidence: 99%
“…According to the bestÞt invasion scenarios, onion thrips adults started invading onion crops at 6 Ð98 d after onion emergence or from mid-June (mid-winter) to mid-September (early spring), depending on site and year. Invasions starting as early as 6 d after onion emergence are surprising but plausible, because trapping data showed that adults were ßying in onion Þelds in small numbers long before the Þrst thrips were detected on onion plants (Mo 2007), and egg monitoring data showed that eggs were laid in onion plants as early as the single-leaf stage (Mo et al 2008). Two of the Þve seasonal patterns were best described with the daily invasion rates of 0.002Ð 0.008 adults/plant, one by a daily invasion Table 2 Numbers in parentheses show the relative widths of the ranges as percentages of the widths of the tested ranges.…”
Section: Discussionmentioning
confidence: 99%
“…For species identiÞcations, subsamples of thrips were slide-mounted and checked under a stereo microscope. Compared with the alcohol-wash method, the in situ inspection method generally underestimates larval densities because of the small size of young larvae and the larval habit of hiding in unexposed areas of the leaves (Mo et al 2008). The degree of underestimation is likely to vary because of variations in levels of concentration of the inspectors and skill differences between different inspectors.…”
Section: Methodsmentioning
confidence: 99%